Design and construction of Water Level Control (WLC) at Minangkabau International Airport - Hendriansyah, Yoga; Islami, Syaiful (Department of Electrical Engineering Universitas Negeri Padang, 2025)
This study aims to design an automatic water pump control system using the Omron 61F-GP-N Water Level Controller (WLC) to overcome energy waste and damage due to manual operation. The system is designed in two modes: automatic based on a water level sensor and manual via a push button, with main components such as a contactor, thermal overload relay (TOR), indicator, and control panel. In automatic mode, the pump turns on when the water is below the lower limit and turns off when it reaches the upper limit. Test results show that the system works according to its expected function, with an average response time of 0.4 seconds between the sensor and the motor. The motor is capable of flowing water of 1.51 m³/minute, with a working current during charging of 9.75 A. The WLC also shows excellent performance with an average voltage of 7.56 V and a current of only 0.08 mA, indicating the efficiency and stability of the sensor's work. In conclusion, this system is effective and applicable, and is able to improve the efficiency and reliability of water pump control. For further development, it is recommended to compare this sensor with other types and design alternative similar sensors that are more economical so that they can be widely used by the community